Increasing Earnings Inequality: Reconciling Evidence from Survey and Administrative Data - Haltiwanger, John; Hyatt, Henry R.; Spletzer, James R. (Journal of Labor Economics, 2023)
Analyses of survey data highlight observable person characteristics, such as education and occupation, as critical factors for rising earnings inequality, while industry has an offsetting effect. In contrast, analysis of administrative data highlights that rising between-firm earnings dispersion and, in turn, between-industry earnings dispersion dominates the rise in earnings inequality. We construct a novel integrated dataset based on CPS micro data linked with LEHD administrative records. We find that most of the rise in earnings inequality is accounted for by rising between-industry inequality. This finding reflects a substantial contribution of increased sorting and segregation of observable person characteristics between industries.